2012
DOI: 10.1021/es3046235
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Transport Modeling of Chromium Isotope Fractionation during Cr(VI) Reduction

Abstract: Chromium isotope fractionation is indicative of mass-transfer processes, such as reduction of Cr(VI) to Cr(III) during groundwater remediation. Laboratory experiments comparing batch and column treatment of Cr(VI) using organic carbon suggest that the associated isotope fractionation may be influenced by solute-transport mechanisms. These batch and column experiments were simulated using the reactive transport model MIN3P to further evaluate the effects of Cr reduction and transport on isotope fractionation un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…A similar two-stage isotope curve was described for the reduction of Cr(VI) by organic carbon under saturated flow conditions in Jamieson- Hanes, Amos, et al (2012). Although preliminary observations identified a linear isotope trend (Jamieson-Hanes, Gibson, et al, 2012), reactive transport modeling suggested a two-mechanism system.…”
Section: Correlating Cr Isotope Behaviour With Reaction Ratementioning
confidence: 57%
See 2 more Smart Citations
“…A similar two-stage isotope curve was described for the reduction of Cr(VI) by organic carbon under saturated flow conditions in Jamieson- Hanes, Amos, et al (2012). Although preliminary observations identified a linear isotope trend (Jamieson-Hanes, Gibson, et al, 2012), reactive transport modeling suggested a two-mechanism system.…”
Section: Correlating Cr Isotope Behaviour With Reaction Ratementioning
confidence: 57%
“…The presence of a complex isotope trend during the reduction of Cr(VI) by ZVI under saturated flow conditions indicates that the application of a single isotope fractionation value may not be sufficient to describe some systems. Previous studies using organic carbon to treat Cr(VI) under static and dynamic flow conditions suggest that a multi-mechanism interpretation may be more appropriate (Jamieson-Hanes, Amos, et al, 2012). A flow-through cell setup such as the one described in this study is valuable because multiple parameters can be monitored concurrently during Cr(VI) treatment to improve characterization of the processes and interpret the isotope data.…”
Section: Influence Of Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Some models consider transport-based fractionation (Eckert et al, 2012;Rolle et al, 2010;Van Breukelen and Rolle, 2012a), or addition of individual isotopic "species" in existing models that are necessary to describe contaminant degradation and sorption reactions (Hunkeler et al, 2009), including the transformation through multiple reaction pathways (Jin and Rolle, 2014). Others incorporate isotopespecific rate laws for mineral dissolution and precipitation that impact radiogenic and radioactive isotopes (Maher et al, 2006b), stable isotope fractionation associated with mineral growth (Druhan et al, 2013), abiotic redox reactions (Jamieson-Hanes et al, 2012;Wanner et al, 2014) and Monod kinetics (Cheng et al, 2016;Druhan and Maher, 2014;Gibson et al, 2011). A key advantage of these approaches is that the major element compositions are directly associated with the isotopic fractionation, enabling more rigorous evaluation of the transformations than could be obtained by considering the elemental or isotopic data in isolation (Sullivan et al, 2016).…”
Section: Integration Of Novel Datamentioning
confidence: 99%
“…Macroscopic or Darcy-scale reactive transport models are now becoming a common means of quantifying stable isotope partitioning by separating the isotopes of interest into individual 'species' that follow parallel reaction networks. The fractionating reaction in these simulations is commonly a homogeneous aqueous process (Dale et al 2009;Gibson et al 2011;Druhan et al 2012Druhan et al , 2014Jamieson-Hanes et al 2012;Wanner and Sonnenthal 2013). To date, models designed to simulate the infl uence of dissolution on the isotope ratio of fl uids rely on the assumption that the solid-phase isotopic composition remains fi xed over time.…”
Section: Dissolutionmentioning
confidence: 99%